STEMinist sensibilities in the promotion of STEM and tech participation to women and girls. - Bennette, Angela; Toffoletti, Kim (Journal of Gender Studies, 2025)
In recent years, organizations aiming to empower women and girls to participate in STEM have proliferated. While the issue of gender inequality in STEM is well documented, little is known about the feminist appeals these organizations make to girls. This study analyses the websites of five Australian 'women in tech' organizations to understand how they frame and respond to the problem of gender inequality, and what feminist sentiments they reflect. Combining a postfeminist sensibility (Gill, 2007) with Myers et al. (2019) concept of STEMinism, we propose a 'STEMinist sensibility' to interpret the ways in which gender issues and subjects are represented on STEM initiative websites. We identify four themes characterizing a STEMinist sensibility: 1) acknowledging the problem and promoting solutions to gender inequality, 2) a focus on tech girls as problem solvers, 3) cultivating community and connection for success, and 4) playing with girlification. We show how websites acknowledge the structural impediments women and girls face, yet simultaneously represent girls as both problematic and as problem-solvers in a way that renders them individually responsible for resolving the problems arising from gender inequality in their fields. These findings have implications for organizations promoting STEM initiatives to women and girls.